Ultraviolet B Phototherapy Intervention in Patients with Multiple Sclerosis: A Prospective, Randomized Pilot Trial - W. Motl, Robert; M. Niemiro, Grace; De Lisio, Michael; Sommer, Sarah; J. Riskin, Barry; A Best-Popescu, Catherine (Journal of Neurological Research And Therapy, 2019)
Background There is substantial evidence, from well-conducted epidemiological studies, that low vitamin D levels are correlated with increased risk for MS, and multiple case control studies have implicated the involvement of vitamin D deficiency in MS etiology. Narrow-band Ultraviolet B (NB-UVB; 300nm - 311 nm) induced vitamin D production has not previously been studied in a multiple sclerosis (MS) randomized placebo-controlled trial (RCT). Objectives To investigate NB-UVB induced vitamin D production, immunomodulation and MS symptomology following NB-UVB phototherapy in a MS cohort. Methods Using a blinded RCT study design, twelve individuals 18 years or older with MS were enrolled and assigned (1:1) into individualized NB-UVB dose (10-30kJ/m) phototherapy, or into placebo treatment, delivered 3 times per week, for 8-weeks. Serum vitamin D levels, walking performance, strength, cognitive function, mood and circulating progenitor cells (CPCs: CD34+CD45dim), monocyte populations (Intermediate CD14+CD16+, Classical CD14+CD16-), and T regulatory cell (CD4+/CD25+/FoxP3+Tregs) count were assesed. The data were analyzed by 2 x 3 mixed factor ANOVA.   Results A statistically significant condition by time interaction on vitamin D levels (F=7.14, p<.005, partial η2=.42) was identified. NB-UVB phototherapy may provide immunomodulation in a select group of MS individuals. Conclusion UVB phototherapy corrects vitamin D deficiency. This study adds to the growing research investigating UVB treatment in MS.
Keywords: Multiple Sclerosis (MS); Ultraviolet B (UVB) radiation; phototherapy; Vitamin D deficiency; 25-hydroxyvitamin D (25(OH)D; and Regulatory T cells (Tregs)